Optimized Drainage System Design for Andesite Mining at PT. Rolas Nusantara Tambang, Kejayan, East Java - Antonius Longan Melang; Avellyn Shinthya Sari; Yazid Fanani (Journal of Earth and Marine Technology (JEMT), 2023)
This study presents a systematic approach to designing a filtration system aimed at efficiently managing rainwater and surface runoff outside mining areas. Utilizing a quantitative method, the data collection predominantly involves secondary sources. The data is processed through a series of steps: rainfall projection, delineation of rainwater catchment areas, calculation of rainfall intensity and inflow rate, and determination of open channel and settling pond dimensions. The designed open channels have a trapezoidal shape with specific dimensions including a base width of 0.51 m, a side length of 0.62 m, a slope angle of 60°, and a channel depth of 0.54 m. These channels span a total length of 2.216 m. The accompanying settling ponds are rectangular with dimensions encompassing a length of 31 m, a width of 11 m, a depth of 6 m, and an area of 341 m². These ponds have a volume capacity of 2,046 m³, achieving an impressive 90.89% efficiency. Notably, maintenance of the settling pond involves periodic dredging using the Kobelco SK200 Excavator at intervals of roughly 16 years (5,817 days). Given that this maintenance duration surpasses the expected mine lifespan, no further interventions are required for the pond during the mine's operational period.